Effect of heat treatment on the corrosion behaviour of bronze alloys printed by laser metal deposition - Tiew, Jia Jing (Nanyang Technological University, 2021)
Additive manufacturing (AM) plays a vital role in Industry 4.0, due to its highly sustainable and cost-efficient factors. Laser metal deposition is one of the well-established metal AM process which promotes repairment and can better create the superior functionally graded material (FGM). Current research on LMD-printed nickel-aluminum bronze is limited, which consists mainly of studies on mechanical property. However, corrosion property of NAB is important due to its wide usage in marine and offshore environment. Hence, this research focused on the corrosion resistance of LMD-printed Cu-9Al-5Fe-5Ni, along with the effect of heat treatment. Heat treatment is a common post-processing technique which alters the microstructure and thus the properties of the alloy. In addition, the parameter of plane orientation was investigated. As-built LMD-NAB performed superbly with low corrosion rate due to its superior surface film resistance. Heat treatment at 675 °C improved its corrosion resistance by 17.2% and 12.6% for XY675 and XZ675, respectively. This is due to the combination of both the increase β’ to α phase transformation on the microstructure and the better resistance of surface film. Further increase in temperature to 900 °C resulted in a drop of 45.5% and 35.9% in XY900 and XZ900, respectively, compared to the as-built samples. The α to β’ phase transformation and weaker surface film resistance were the reasons for this result. Finally, heat treatment at 1030 °C continued to worsen the alloy’s corrosion resistance as corrosion-prone β’ phase increased, even though resistance of surface film rose. Corrosion resistance fell by 57.9% and 52% for XY1030 and XZ1030, respectively, compared to the as-built counterparts. Corrosion resistance of XZ-C samples were far superior to that of XY-C samples. In general, this can be attributed to the better film resistance of XZ-C compared to XY-C. However, an exception was observed for XY900 and XZ900, where XZ-C attained worse film resistance, but overall better corrosion resistance. All in all, XZ675 performed exceptionally as compared to the rest of the samples. Heat treatment at 675 °C created an outstanding corrosion resistance of the alloy, especially for the XZ-C plane-oriented samples.